The Influence of Employees’ Job Satisfaction Factors on Organizational Commitment - Anis Eliyana; Ria Mardiana Yusuf; Koko Prabowo (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
This research aims to examine about organizational commitment in relation to the job satisfaction factors. Research is conducted on the production employees of PT Jaya Readymix Concrete (JYC) which amounted to 47 people. Data is collected from the questionnaire that was given directly to the respondent. Analysis techniques used in research is regression analysis between factors of employees’ job satisfaction as independent variables, which consists of the ability utilization, compensation, relationship with co-workers, working conditions, recognition and achievement with organizational commitment as dependent variables. Based on the results of the regression analysis of linear regression model equations, we derived  a formulation as follows: Y = -1.012 + 0.184X1 + 0.581X2 + 0.080X3 + 0.118X4 + 0.136X5 + 0.165X6 + e.  Results show that the job satisfaction factors simultaneously have a significant effect on organizational commitment in JYC with the coefficient of determination (R2) is 0.967, and that compensation is the dominant variables influencing employee's organizational commitment in the production department at JYC.